Investigating Students’ Motivation on the Use of Rosetta Stone in Learning English Pronunciation - Sri Yuliani; Khulaifiyah Khulaifiyah; Andi Idayani (STAI Hubbulwathan Duri, 2023)
English as a Foreign Language teaching and learning has made extensive use of the integration of multimedia language such as Rosetta Stone. Therefore, this research aims to find out Junior High school students' motivation in learning pronunciation by using the Rosetta Stone in three dimensions of self-determination theory in terms of autonomy, competence and relatedness. The quasi-experimental pretest-posttest design with 30 samples divided into two groups was used in this methodology. The experimental group received face-to-face instruction using Rosetta Stone, while the control group only received instruction using the drilling technique. Furthermore, the result of statistical analysis showed a significant difference between the groups in terms of total support for the experimental group. As a result, Rosetta Stone inspired students to participate in the pronunciation class, and they are enthusiastic and satisfied with the use of Rosetta Stone in the classroom.